TRANSFORMASI HUNIAN VERNAKULAR SUKU DUANU, PESISIR TIMUR SUMATERA - Gun Faisal (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
Ethnic Duanu is a part of Proto-Malay who came in the first migration group to Austronesian territory. They were mostly found as sea-gypsy who live on canoes that was close to sea shore area. Along with time and acculturation, today’s Duano people have starting inhabit at seaside area, and are dwelling at stilt house which is found as a vernacular house pattern. Therefore, this is interesting to investigate how transformation of the pattern. Qualitative research approach in rationalistic paradigm is used in this research. By focusing on looking at changes in pattern of shape and space, daily values, perceptions, as well as on other ongoing changes at Duanu. The findings in the field show that the transformation of the Duanu’s house are occured due to acculturation and negociation of daily cultural life, accepting update outside information that come to Duanu people, and is also through government intervention.